2013
DOI: 10.2466/02.15.pr0.113x24z5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Predictions of the Brooding and Reflection Subscales of the Japanese Ruminative Responses Scale for Depression

Abstract: The Ruminative Responses Scale (RRS) is a measure of depressive rumination which has two subscales: Brooding and Reflection. This article examines the longitudinal predictions for depression and the test-retest reliability of the Brooding and Reflection of the Japanese RRS. Japanese university students (N = 378) completed the RRS, the Center for Epidemiologic Studies Depression Scale (CES-D), and the Inventory to Diagnose Depression, Lifetime Version (IDDL) which was modified to assess symptoms experienced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Brooding did not predict depression assessed at subsequent time points. Hasegawa et al ( 2013 ) previously showed that the RRS total scale had greater predictive power than did the brooding subscale for depression assessed 8 weeks later. The weak predictive power of the brooding subscale may be due to relatively weak internal consistency ( αs ranged from .78 to .82) and a narrower range of subscale scores ( SDs ranged from 3.92 to 3.96) than the RRS total scale ( αs ranged from .91 to .93, and SDs ranged from 13.04 to 13.84; see Table 1 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Brooding did not predict depression assessed at subsequent time points. Hasegawa et al ( 2013 ) previously showed that the RRS total scale had greater predictive power than did the brooding subscale for depression assessed 8 weeks later. The weak predictive power of the brooding subscale may be due to relatively weak internal consistency ( αs ranged from .78 to .82) and a narrower range of subscale scores ( SDs ranged from 3.92 to 3.96) than the RRS total scale ( αs ranged from .91 to .93, and SDs ranged from 13.04 to 13.84; see Table 1 ).…”
Section: Discussionmentioning
confidence: 98%
“…Previous experimental studies have shown that inducing rumination increases negative mood in dysphoric participants (Nolen-Hoeksema and Morrow 1993 ; Lyubomirsky and Nolen-Hoeksema 1995 ; Lyubomirsky et al 1999 ; Lavender and Watkins 2004 ). Higher total scores on the Ruminative Responses Scale (RRS; Nolen-Hoeksema and Morrow 1991 ) have been found to be predictive of more severe depression (Nolen-Hoeksema and Morrow 1991 ; Hasegawa et al 2013 ) and the onset of major depressive episodes (Nolen-Hoeksema 2000 ; Spasojević and Alloy 2001 ). Two factors that have been extracted from the RRS include brooding , which involves “a passive comparison of one’s current situation with some unachieved standard,” and reflection , which is “a purposeful turning inward to engage in cognitive problem solving to alleviate one’s depressive symptoms” (Treynor et al 2003 , p. 256).…”
Section: Introductionmentioning
confidence: 99%
“…Hasegawa (2013 ) reported that Brooding, Refl ection, and total RRS scale scores have good internal consistencies (αs = .81, .75, and .93, respectively) and moderate 4-week test-retest reliabilities ( r s = .59, .72, and .75, respectively). These values are identical to those reported for the original scale ( Treynor, et al ., 2003 ; see also Hasegawa, Koda, Hattori, Kondo, & Kawaguchi, 2013 ). Confi rmatory factor analysis indicated that the model, which assumed that Brooding and Refl ection are diff erent factors, fi t the data well (CFI = 0.92, RMSEA = 0.08).…”
Section: Methodsmentioning
confidence: 98%
“…Also, levels of brooding rumination mediate the relationship between childhood trauma and depressive symptoms (Raes & Hermans, 2008). Reflective rumination has predominantly been found to have either a protective effect or no relationship with future depressive symptoms (Burwell & Shirk, 2007;Cox, Funasaki, Smith, & Mezulis, 2012;Grossmann & Kross, 2010;Hasegawa, Koda, Hattori, Kondo, & Kawaguchi, 2013;Siegle et al, 2004;Treynor et al, 2003). One study found that reflective rumination is predictive of brooding rumination but is not associated with depressive symptoms (Takano & Tanno, 2009).…”
Section: Introductionmentioning
confidence: 99%